2018
DOI: 10.2106/jbjs.17.01149
|View full text |Cite
|
Sign up to set email alerts
|

Patient Risk Factors Do Not Impact 90-Day Readmission and Emergency Department Visitation After Total Ankle Arthroplasty

Abstract: Prognostic Level IV. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 16 publications
0
17
1
Order By: Relevance
“…Previous literature described that with TAA, higher comorbidity was not associated with readmission 20 , failure 14 , or revision 21 . However, the adverse impact of comorbidities on TAA complication has been previously documented by several authors 22 , 23 .…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Previous literature described that with TAA, higher comorbidity was not associated with readmission 20 , failure 14 , or revision 21 . However, the adverse impact of comorbidities on TAA complication has been previously documented by several authors 22 , 23 .…”
Section: Discussionmentioning
confidence: 76%
“…Previous studies measured comorbidity with Deyo-Charlson index, without differentiating each comorbidity 7 , 14 , 21 . In addition, there are few large series in which all the comorbidities have been assessed concomitantly 20 , 24 .…”
Section: Discussionmentioning
confidence: 99%
“… 24 , 25 , 26 In invasive thoracic surgeries, 30-day ED visit rates following thoracotomy for pleuropulmonary disease, coronary artery bypass grafting, and esophagectomy were 6%, 27 12%, 28 and 16%, 29 respectively. Concerning orthopedic procedures, ED visit rates in the 1-month period following total hip or knee replacement surgery and the 90-day period following total ankle arthroplasty were 6% 30 and 3.5%, 31 respectively. In spine surgery specifically, Pak et al 32 reported a 30-day postoperative ED visit rate of 15% after common procedures such as lumbar arthrodesis, diskectomy, and decompression with the primary complaint being low back pain.…”
Section: Discussionmentioning
confidence: 99%
“…7,12,19,21 Within the TAA literature, however, relatively few studies have examined length of stay, post–acute care, or readmissions in a bundled payment context, and none have examined how often costs exceed the bundled payment target. 1,4-6…”
mentioning
confidence: 99%
“…7,12,19,21 Within the TAA literature, however, relatively few studies have examined length of stay, post-acute care, or readmissions in a bundled payment context, and none have examined how often costs exceed the bundled payment target. 1,[4][5][6] The purpose of this study was to (1) determine the rate at which TAA costs exceed the CJR target payments (primary outcome), (2) investigate patient demographics and comorbidities associated with exceeding CJR targets, and (3) compare these results with a similar institutional cohort of total hip and knee arthroplasty cases performed during the same period.…”
mentioning
confidence: 99%